Monkeypox and other orthopoxvirus zoonoses - K. N. Gruzdev (Ветеринария сегодня)
The paper highlights the current knowledge on infection biology, epidemiology and evolution of monkeypox virus (MPXV), cowpox virus (CPXV), buffalopox virus (CPXV), camelpox virus (CMLPV), as well as addresses some factors that modulate dynamics of orthopoxvirus transmission, manifestation of orthopoxvirus infections and their preservation in nature. Despite the elimination of the historically infamous smallpox, orthopoxviruses remain a serious veterinary and health problem. Their role is currently increasing while the number of persons not immune to smallpox grows. Along with this, there is a genetic transformation of pathogens. In this regard, the risks of human infection with orthopoxviruses of zoonotic nature are increasing. The problem of monkeypox, cowpox, buffalopox and camelpox and the respective agents included in the genus of zoonotic orthopox viruses presents the greatest interest. Along with the increased number of human monkeypox cases in 2020–2022, a retrospective analysis of the last 20 years shows that the activity of monkeypox outbreaks in the XXI century intensified in Central African countries. Cowpox outbreaks in Europe and camelpox outbreaks in Southwestern and Central Asia have also become more active. In 2011, in India, the camelpox virus overcame the interspecies barrier and caused a clinical pox-like disease in humans. Scientists are alarmed by these facts as the camelpox virus genomeis 99% homologous to the genome of the small poxvirus. This requires strengthening the epizootological and epidemiological monitoring of orthopoxvirus zoonotic pathogens.